1996
DOI: 10.2166/wst.1996.0570
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of long-chain fatty acid to anaerobic sludges from various origins

Abstract: Seven anaerobic sludges were screened in order to obtain the most suitable methanogenic inoculum for the anaerobic treatment of wastewaters containing long-chain fatty acids (LCFA). The selection was made on the basis of the toxicity of a model compound, oleate, to acetoclastic methanogens in different sludges. The effects of three biological factors, sludge origin, specific acetoclastic methanogenic activity and sludge adaptation to lipids, and a physical factor, specific surface area of sludge, on the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 0 publications
9
69
0
2
Order By: Relevance
“…It appears that the propagated ultrasonic wave generated the numerous craters on the surface of the methanogenic granules; the greater amount of produced biogas resulted in much bigger and deeper cracks than the control granules. As a result of a rougher and more uneven surface, 2.3 times higher specific surface area was observed from the ultrasonicated granules (0.5337 ± 0.0036 m 2 /g TS) than the control granules (0.1624± 0.0025 m 2 /g TS), which were in a range of previously reported values (0.02-0.074 m 2 /g TS) (Hwu et al, 1996). Higher specific surface area, implying an increase of the contact frequency between the substrate and microorganism, appears to be a more favorable condition for the microbial reactions.…”
Section: Scanning Electron Microscope and Specific Surface Areasupporting
confidence: 76%
“…It appears that the propagated ultrasonic wave generated the numerous craters on the surface of the methanogenic granules; the greater amount of produced biogas resulted in much bigger and deeper cracks than the control granules. As a result of a rougher and more uneven surface, 2.3 times higher specific surface area was observed from the ultrasonicated granules (0.5337 ± 0.0036 m 2 /g TS) than the control granules (0.1624± 0.0025 m 2 /g TS), which were in a range of previously reported values (0.02-0.074 m 2 /g TS) (Hwu et al, 1996). Higher specific surface area, implying an increase of the contact frequency between the substrate and microorganism, appears to be a more favorable condition for the microbial reactions.…”
Section: Scanning Electron Microscope and Specific Surface Areasupporting
confidence: 76%
“…1(b)]. Although it is biodegradable, anaerobic metabolism of vegetable oil may produce intermediates that are inhibitory to aceticlastic methanogens and hydrogen-producing acetogens (Hanaki et al, 1981;Koster and Cramer, 1987;Hwu et al, 1996;Lalman and Bagley, 2001). Such inhibition was observed during anaerobic degradation of vegetable oil in freshwater sediments (Li et al, 2001(Li et al, , 2005.…”
Section: Resultsmentioning
confidence: 99%
“…Free long-chain fatty acids have been reported to be toxic to a wide variety of microorganisms in anaerobic digestion systems (Hanaki et al, 1981;Koster and Cramer, 1987;Rinzema et al, 1994;Hwu et al, 1996;Lalman and Bagley, 2001;Pereira et al, 2001Pereira et al, , 2003a. Transient sediment toxicity was also observed during the anaerobic biodegradation of vegetable oil in freshwater sediments (Li and Wrenn, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although some information was known about modeling of MWWTFs, the demand for a more complete operational picture called for increased model complexity. For example, it was found that long-chain fatty acids produce various toxic effects during anaerobic digestion [6,7]. Anaerobic digestion refers to the reduction of sludge mass through bacterial metabolism in the absence of oxygen.…”
Section: Lipid Origins In Wastewater Treatment Facilitiesmentioning
confidence: 99%